Answer:
1. $3,130
2. $3,190
3. $4,970
4. $2,130
5. $690
Step-by-step explanation:
The computation is shown below:
We know that,
The ending balance of retained earning = Beginning balance of retained earnings + net income - dividend paid
So according to this formula, we solve each parts
1. Dividend = Net income - increase in retained earnings
= $4,410 - $1,280
= $3,130
2. The ending balance of retained earning = Beginning balance of retained earnings + net income - dividend paid
= $2,530 + $850 - $190
= $3,190
3. Net income = increase in retained earnings + dividend
= $3,480 + $1,490
= $4,970
4. The Beginning balance of retained earnings = ending balance of retained earning + dividend - net income
= $2,190 + 550 - $610
= $2,130
5. Dividend = Net income - increase in retained earnings
= $1,300 - $610
= $690